Smart sensor systems emerging technologies and applications - Meijer, G. C. M. (Gerard C. M.); Pertijs, Michiel A. P.; Makinwa, Kofi A. A. (Wiley, 2014)
Taking a multidisciplinary approach to review recent developments in the field of smart sensor systems, this book provides complete coverage of all important system and design aspects, their building blocks, and methods of signal processing